Unveiling the Pathways from Parenting to Entrepreneurship: A Structural Equation Modeling Approach - Maulana Amirul Adha; Nova Syafira Ariyanti; Ferry Setyadi Atmadja; Mayang Riyantie; Nina Farliana; Rudy Ansar (Bright Publisher, 2026)
This study investigates how parenting styles influence vocational students’ entrepreneurial intentions and career choices, considering self-efficacy and entrepreneurial attitudes as mediating variables. Using a quantitative approach, data were collected from 381 vocational school students and analyzed with Structural Equation Modeling (SEM) using AMOS 24. The participants consisted of 55.7% females and 44.3% males, representing families from low-, middle-, and high-income groups based on the 2024 Jakarta provincial minimum wage, with parents working as civil servants, private-sector employees, entrepreneurs, and others. The results indicate that authoritative parenting positively fosters entrepreneurial intentions and encourages students to pursue entrepreneurship as a career path. Furthermore, the mediating roles of self-efficacy and entrepreneurial attitudes are confirmed, providing a clearer explanation of how parenting influences entrepreneurial career decisions. The study contributes theoretically by extending models of entrepreneurial intention with family socialization factors, and practically by offering a tested framework to guide efforts in promoting entrepreneurship among vocational students.